PROTON RADIATION THERAPY: CLINICAL APPLICATION OPPORTUNITIES AND RESEARCH PROSPECTS - M. V. Zabelin; V. A. Klimanov; J. J. Galyautdinova; A. S. Samoilov; A. O. Lebedev; E. V. Shelyhina (Исследования и практика в медицине)
This article is the review of literature concerning use of proton beam therapy in treatment of oncology. The staticized data on comparison of effi ciency of this method at an eye melanoma are lit. Advantages of proton therapy on the level of local control and depression of frequency of development of the radio induced cataract are refl ected in the provided data. In evident material the technology of preparation and carrying out radiation of an eye is shortly covered with a fascicle of protons. The experience of use of proton therapy of tumors of a skull base got for the last several decades, showed good results. Physical properties of a fascicle of protons allow to achieve the maximum dose conformality, having lowered, thereby, a radial load on the next crucial anatomical structures. The presented material on an oncopediatrics shows insuffi cient knowledge of scientists concerning advantage of a fascicle of protons over modern methods of photon radiation. There are only preliminary clinical results concerning generally of treatment of cranyopharyngiomas. At cancer therapy of a mammary gland, proton therapy showed the best local control of postoperative recurrent tumors, and also depression of a dose load on the contralateral party. The available results of the retrospective analysis of clinical data in the University medical center of Lome Linda, testify to advantages of proton therapy of the localized prostate cancer. The lack of a biochemical recurrence and a local tumoral progression within 5 years after radiation was shown. The data obtained from experience of use of proton radiation therapy with passively scattered fascicle for cancer therapy of a prostate at an early stage showed the admixed results in comparison with modern methods of radiation therapy with the modulated intensity. In treatment of non-small cell cancer of mild advantage of proton therapy aren’t absolutely proved yet. There are data on extreme toxicity of a combination of a chemotherapy and photon radiation. It is supposed that physical properties of protons will allow to reduce toxicity of such technique, however clinical trials in comparison of protons and RTMI aren’t fi nished yet. The main directions of development of a method of proton therapy are shortly lit.